INOVASI PEMASARAN DIGITAL DAN KEMASAN PRODUK UMKM MAKANAN RINGAN UNTUK DAYA SAING PENJUALAN - Nurita Widianti; Novita Widyaningrum; Sri Tutie Rahayu; Irsat Surya Sekti; Rizka Noor Miftakhul Ulum; Lia Retian Asrifah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This Community Service Program (PKM) was implemented to address the challenges faced by the SME CV. Sido Makmur in Bandungan Subdistrict, Semarang Regency, which continues to face obstacles in conventional marketing, simple packaging, limited production technology, and manual financial record-keeping. Implementation methods included field surveys, situation analysis, interviews, solution planning, training, digital marketing mentoring, packaging design development, the application of appropriate technology, and the implementation of an Android-based financial application. The results of the activities showed a significant improvement in five key aspects of the partner’s business. On the production side, the use of a mechanical mixer replaced manual mixing, thereby improving efficiency and consistency in quality. In terms of packaging, products that were previously plain now feature informative designs with brand labels, ingredient lists, and moisture-resistant materials. Digital marketing, which was previously limited to local wholesale stores, has expanded through online marketplaces and social media, broadening market reach. Financial management, which was previously manual, is now more accurate with the SI-APIK app, supporting automated record-keeping and routine reporting. Additionally, human resource capacity has increased through digital literacy and managerial training. Overall, the integration of innovations in digital marketing, packaging design, production technology, and app-based financial systems has proven to strengthen the competitiveness of partner SMEs. This program not only resolves operational challenges but also provides a practical foundation for business sustainability, while making a tangible contribution to SME empowerment and the strengthening of the local economy. ABSTRAK Program Pengabdian kepada Masyarakat (PKM) ini dilaksanakan untuk menjawab persoalan yang dihadapi oleh UMKM CV. Sido Makmur di Kecamatan Bandungan, Kabupaten Semarang, yang masih terkendala dalam pemasaran konvensional, kemasan sederhana, keterbatasan teknologi produksi, serta pencatatan keuangan manual. Metode pelaksanaan meliputi survei lapangan, analisis situasi, wawancara, perencanaan solusi, pelatihan, pendampingan digital marketing, pengembangan desain kemasan, penerapan teknologi tepat guna, serta implementasi aplikasi keuangan berbasis Android. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada lima aspek utama usaha mitra. Dari sisi produksi, penggunaan mixer mekanis menggantikan pengadukan manual sehingga meningkatkan efisiensi dan konsistensi kualitas. Pada aspek kemasan, produk yang sebelumnya polos kini memiliki desain informatif dengan label merek, komposisi, dan material tahan lembap. Pemasaran digital yang semula terbatas pada toko grosir lokal berkembang melalui marketplace dan media sosial, memperluas jangkauan pasar. Pengelolaan keuangan yang sebelumnya manual kini lebih akurat dengan aplikasi SI-APIK, mendukung pencatatan otomatis dan laporan rutin. Selain itu, kapasitas sumber daya manusia meningkat melalui pelatihan literasi digital dan manajerial. Secara keseluruhan, integrasi inovasi dalam pemasaran digital, desain kemasan, teknologi produksi, dan sistem keuangan berbasis aplikasi terbukti memperkuat daya saing UMKM mitra. Program ini tidak hanya menyelesaikan permasalahan operasional, tetapi juga memberikan fondasi praktis bagi keberlanjutan usaha, sekaligus berkontribusi nyata terhadap pemberdayaan UMKM dan penguatan ekonomi lokal.